Claustrophobic Tendencies and Continuous Positive Airway Pressure Therapy Non-adherence in Adults with Obstructive Sleep Apnea - Edmonds, Janalyn Cantey (Heart Lung, 2015)
OBJECTIVES: (1) Determine frequency of claustrophobia in adults with obstructive sleep apnea (OSA) after first CPAP night; and (2) determine if claustrophobia influences CPAP adherence. BACKGROUND: Claustrophobia is a common clinical problem among CPAP-treated OSA adults yet few studies have examined the problem. METHODS: Secondary analysis of data from prospective, longitudinal study of adults with OSA (n=97). CPAP-Adapted Fear and Avoidance Scale (CPAP-FAAS) collected immediately after CPAP titration polysomnogram. The primary outcome was objective CPAP use at 1 week and 1month. RESULTS: Sixty-three percent had claustrophobic tendencies. Females had higher CPAP-FAAS scores than males. FAAS ≥25, which is a positive score for claustrophobic tendencies, was significantly influential on CPAP non-adherence at 1 week (aOR= 5.53, 95% CI 1.04, 29.24, p=0.04) and less CPAP use at 1month (aOR= 5.06, 95% CI 1.48, 17.37, p=0.01) when adjusted for body mass index and CPAP mask style. CONCLUSION: Claustrophobia is prevalent among CPAP-treated OSA adults and influences both short-term and longer-term CPAP non-adherence. Interventions are needed to address this treatment-related barrier.